Injuries to the knee structures in soccer (Research, Society and Development, 2021)
Knee injury rates in soccer players are extremely high when compared to other types of injuries or other groups of athletes. This reality can be attributed to the greater exposure to shock in this joint or the high training load to which these athletes are constantly submitted. The objective of this work was, through an Integrative Literature Review from the Virtual Health Library (VHL) databases: Scielo, Lilacs, Capes Periodicals and Pubmed, to know these indexes, identify which structures are most affected and observe if there is a relationship between the occurrence of the injury and the position in which the player acts. A significant number of articles were found that showed, among other things, that defenders and strikers are the groups most likely to be injured due to the high number of jumps performed during matches, making evident the need to improve these and other movements. Still, we realize the need for new studies that better identify the factors involved in knee injuries and describe the best strategies for preventing these injuries that negatively impact the careers of these athletes.